The measurement of mechanical parameters in machines - Raevskii, N. P. (Pergamon Press, 1965)
The Measurement of Mechanical Parameters in Machines is a translation from the Russian version and presents methods used in the U.S.S.R. for measuring mechanical properties. This book discusses different indicators and accepted methods of measuring separate parameters. This text also explains the metrological characteristics of mechanical parameters that can be determined by applying the equations of motion, usually represented as equations of kinetic energy or as a Lagrangian equation. The electrical methods of measuring machines and recording results are noted, and the kinds of methods pref.